Postoperative Heart Failure with Preserved Ejection Fraction Induced by Flumazenil Administered for Remimazolam Antagonism - Keito Koh; Takeshi Omae; Sonoko Sakuraba; Masateru Kumemura; Sho Yamazaki; Hiroshi Yunoki (Case Reports in Anesthesiology)
Remimazolam is an ultrashort-acting benzodiazepine intravenous anesthetic characterized by rapid awakening after anesthesia. However, the method for administering remimazolam in clinical practice remains unclear. Here, we report a case of postoperative heart failure with preserved ejection fraction (HFpEF) after antagonizing remimazolam with flumazenil. An 82-year-old woman was scheduled to undergo lumbar laminectomy for lumbar spinal canal stenosis. Preoperative echocardiography revealed normal left ventricular systolic function, left atrial enlargement, and impaired left ventricular diastolic function. General anesthesia was induced with 10 mg/kg/h remimazolam and maintained with 0.8 mg/kg/h remimazolam intraoperatively. Before extubation, a total of 1.0 mg of flumazenil was administered. After extubation, the patient developed pulmonary edema due to HFpEF. When remimazolam is administered in elderly patients with cardiac dysfunction, the maintenance dose should be customized according to the patient’s general condition to minimize the dosage of flumazenil.